Regenerative capacity of the enteric nervous system after ileoileal anastomoses in a rat model - Pfeifle, Viktoria Amanda; Frongia, Giovanni (European journal of pediatric surgery, 2017)
Purpose The aim of the study was to investigate the regeneration and migration of neuronal progenitor cells of the enteric nervous system during wound healing after intestinal anastomosis in the rat ileum. Methods Experiments were performed in a rat model of ileoileal anastomosis. Rats were humanely killed on day 2 or day 10 after anastomosis, and the anastomotic region was compared with ileum of healthy rats. Immunofluorescent staining was performed with protein gene product 9.5, nestin, and S100 antibodies. Ganglia of the anastomotic region in both the myenteric and submucosal plexus were counted, and their diameters were measured and compared between groups. Results Analysis of number and diameter of ganglia in both myenteric and submucosal plexus showed individual alterations as a reaction to the surgical manipulation. Significantly less ganglia were found in the submucosal plexus in the operated groups at both day 2 (p < 0.01) and day 10 (p < 0.01) than in the control group. In the myenteric plexus in the operated group, there was a difference in the number of ganglia at day 2, but ganglia count had recovered at day 10 and was not significantly different from the control group. However, the diameter of ganglia in the myenteric plexus still significantly decreasing on day 10 after surgery than in the control group (p = 0.046). Nestin and S100 double-staining showed an increased expression of nestin around the anastomotic wound. Conclusion Our findings suggest a regenerative potential of the enteric nervous system after the surgical ileoileal anastomosis. The myenteric plexus appears to recover faster than the submucosal plexus. This recovery might be driven by nestin-positive neuronal progenitor cells.
Publikationsdatum: 27. Juli 2016 (online)
Gesehen am 24.09.2018